TRANSAKSI E-COMMERCE DALAM PERSPEKTIF EKONOMI SYARIAH - Siti Kholijah (LPPM STAI DARUSSALAM LAMPUNG, 2020)
Advances in technology and communication have changed the mindset of a person, especially the Islamic community in the use of online media. This is marked by the increasing number of sellers and consumers in online transactions, starting from offering goods to marketing to making transactions. Indonesia has the potential to develop e-commerce transactions. However, Indonesia is the most populous Muslim country in the world, so that we cannot forget the provisions of Islamic law in terms of trade. Considering that E-Commerce is carried out via computers and networks, there are several conditions that must be investigated further to ensure the validity of transactions. First, there must be a clear description of the product being traded. Second, both parties must receive a message to obtain confirmation of the agreement (including the contract). Third, there must be continuity in these communications, either through messages or consultations between the seller and the buyer. Overall, E-Commerce does not conflict with Islamic law as long as it fulfills the things contained in a contract according to Islamic binding law.